(untitled) (Quinto Sol, 2022)
In mid- 1919, in the midst of a convulsive political and cultural climate, the Association for Women´s Rights, created and directed by M.D. Elvira Rawson de Dellepiane, in alliance with the deputy of the Unión Cívica Radical, Rogelio Araya, presented two projects: in the Chamber, Civil Emancipation of Women and Women´s Suffrage, the latter the first legislative project for women´s political rights in Argentina and the region. This essay explores the innovative strategies used to transfer the feminist struggle to the venue legislative and also the reasons why despite the efforts put into the endeavor, the project floundered.